1=5(x-4)-2x=

Simple and best practice solution for 1=5(x-4)-2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=5(x-4)-2x= equation:



1=5(x-4)-2x=
We move all terms to the left:
1-(5(x-4)-2x)=0
We calculate terms in parentheses: -(5(x-4)-2x), so:
5(x-4)-2x
We add all the numbers together, and all the variables
-2x+5(x-4)
We multiply parentheses
-2x+5x-20
We add all the numbers together, and all the variables
3x-20
Back to the equation:
-(3x-20)
We get rid of parentheses
-3x+20+1=0
We add all the numbers together, and all the variables
-3x+21=0
We move all terms containing x to the left, all other terms to the right
-3x=-21
x=-21/-3
x=+7

See similar equations:

| b+1/2=1/12 | | y–17=-17 | | 3(1-9x)+4x=-43 | | 12=3w+21 | | 10(2x+2)=16x-16 | | 88=12+x | | 8=5r=-2 | | -100u-156-16u^2=0 | | -3b-5=16 | | 10x+25=50x | | -96=-4c | | 20^(3x)=0.001 | | 3(w+4)+2w=27 | | 7+6x=-33+-2x | | d=0.8571428571= | | 1/4x-22=13 | | 8x-6°=98° | | 84=4/9x+1/5x | | a-5a=-8a | | 5x+17=-37-4x | | 7+6x=33+-2x | | 10x+25=50x= | | 9+3x=2x-1=67 | | 4(n-3)+2n=12* | | 3/3a+14=8 | | 107-12x=66 | | 2/9-5n/18=1/9 | | -6k–3=39 | | 12x-35=-83 | | 4(y-1)=6y+8-3(-4y-2) | | C=20.00-0.07x | | l=4, |

Equations solver categories